A natural triploid in Trichomycterus davisi (Siluriformes, Trichomycteridae): mitotic and meiotic characterization by chromosome banding and synaptonemal complex analyses - Borin, L. A.; Martins-Santos, I. C.; Oliveira, C. (Kluwer Academic Publ, 2002)
Within a total of 50 analyzed specimens a male individual of Trichomycterus davisi has been recorded with 81 chromosomes including 60 metacentric, 18 submetacentric and three subtelocentric chromosomes. When compared with diploid individuals (2n = 54) and the morphological standard of chromosomes, this male is a triploid with 3 = 81 chromosomes. Since staining with silver nitrate indicates three active nucleolar organizer regions (NORs), the three NOR- bearing chromosomes in this individual are genetically active. Analysis of the synaptonemal complex (SC) by electronic microscopy shows that there is an incomplete pairing of the third set of chromosomes in the triploid individual.
Keywords: chromomycin A(3); karyotype; NOR band; synaptonemal complex; Trichomycterus davisi; triploid